Effects of Promotion and Compunction Interventions on Real Intergroup Interactions: Promotion Helps but High Compunction Hurts - Greenland, Katy; Xenias, Dimitrios; Maio, Gregory R. (Frontiers in Psychology, 2017)
Intergroup contact is probably the longest standing and most comprehensively researched intervention to reduce discrimination. It is also part of ordinary social experience, and a key context in which discrimination is played out. In this paper, we explore two additional interventions which are also designed to reduce discrimination, but which have not yet been applied to real intergroup interactions. The promotion intervention encourages participants to relax and enjoy an interaction, while the compunction intervention motivates participants to avoid discrimination. Across two studies, we tested the separate effects of promotion (Study 1) and then compunction (Study 2) on participants’ interactions with a confederate whom they believed to have a history of schizophrenia. In Study 1, participants received either a promotion intervention to ‘relax and have an enjoyable dialogue’ or no intervention (control) (n= 67). In Study 2, participants completed a Single-Category Implicit Attitude Test before being told that they were high in prejudice (high compunction condition) or low in prejudice (low compunction condition) (n= 62). Results indicated that promotion was associated with broadly positive effects: participants reported more positive experience of the interaction (enjoyment and interest in a future interaction), and more positive evaluations of their contact partner (increased friendliness and reduced stereotyping). There were no effects on participants’ reported intergroup anxiety. In contrast, high compunction had broadly negative effects: participants reported more negative experiences of the interaction and more negative evaluations of their contact partner (using the same dependent measures outlined above). In addition, participants in the high compunction condition reported increased intergroup anxiety and increased self-anxiety (anxiety around thinking or doing something that is prejudiced). Participants in the high compunction condition also reported reduced expectancies of self-efficacy (i.e., they were less confident that they would be able to make a good impression).